Killing for the Grade - Arzadon, Maria Mercedes E. (Silliman Journal, 2022)
Using Bourdieu’s concepts of social reproduction, this study examined parental involvement of teachers in the context of “academics arm race” (Demerath, 2009). This study assumes that teachers as parents are supposed to be able to negotiate more skillfully in the educational realm given their forms of capital and knowledge of the various forms of curriculum. Lareau (2003) cited in general terms that parents’ occupational and educational statuses influence parental involvement. The specific sociohistorical–economic context in the Philippines is marked by hyperinflating educational market, dwindling educational budget, and the meager teacher salary. This context plus the honor and award system of the public school system reproduces a certain hypervigilant parenting that will ensure access to quality yet affordable education for their children. Critical pedagogy offers an alternative vision of resistance and cultural production through the formation of communities, collaborative efforts, and reimagining of identities. Critical pedagogy would also entail deconstructing orthodoxy to reveal the real foes, to demand that the state reclaims its stewardship over its youth’s education, and to regulate the predatory market. Such moves will make schools more meritocratic, safer for children, and less prone to inequity.